Legal Protection of Children as Commercial Sex Workers in Human Trafficking Crime - Intan Syapriyani (Ius Poenale, 2020)
Child protection is any effort made to create conditions so that every child can carry out their rights and obligations for the development and growth of children naturally, physically, mentally and socially. Child protection activities bring legal consequences, both in relation to written law and unwritten law. But in Indonesia the enforcement of human rights does not seem to pay much attention to aspects of child protection. The high crime rate of child trafficking shows that the government's efforts to protect child protection are not yet serious. The research method used is a normative juridical approach. The data used in this paper is data obtained from library materials. The results of this study note that the form of protection provided by Law No. 35 of 2014 concerning Child Protection is stipulated in Article 68 which states that special protection for child victims of abduction, sale and / or trafficking is carried out through surveillance, protection, prevention efforts, care and rehabilitation. While the protection of children as victims of trafficking in persons, based on the law. Number 21 of 2007 concerning Eradication of Trafficking in Persons Crimes regulates the protection of witnesses and victims, criminal acts carried out under the Law. Number 13 of 2006 concerning Protection of Witnesses and Victims. The protection model based on Law Number 21 Year 2007 regarding PTPPO does not differentiate between children and adults. Victim witnesses and reporters in child cases must receive protection and legal assistance. The implementation of the Child Protection Act (UUPA) in Indonesia is still very difficult to be taken seriously and is still an obstacle. The reason is none other than the number of people who have become consumers or users of child sex worker services.